Iqbal’s Antagonism towards Pseudo-Mysticism - Abdul Razak, Mohd Abbas; Haneef, Sayed Sikandar Shah; M M Yusoff, Mahathir (2021)
Ever since time immemorial, there has been a constant search in people of all religious traditions to unravel the mystery on how man arrived on this planet and what should be his ideal relationship with God and other life forms. Though all religions have their rituals and doctrine to explain on the God-Man relationship, for some the hunger and thirst to understand God at a much deeper level take them to the path of mysticism. For such people, religion is the outward journey of man towards God, while mysticism is the inward journey of the human soul towards the Absolute. Although mysticism is good as a soul elevating experience, nevertheless at times it can take people away from the reality of life into the other worldliness causing problem to their earthly existence; obligation towards family, society, nation and humanity. The present study is geared towards understanding Iqbal’s views on mysticism. As a mystic-poet and philosopher, at one point of time in his life, Iqbal took great interest in Islamic Mysticism (Tasawwuf); particularly ideas presented by Ibn Arabi (1165-1240) a 12th century Sufi scholar. Later, after his travel and studies in Europe and his eventual involvement in politics, Iqbal took an antagonistic stand against some aspects of Sufism. Through this study, the research team would like to investigate as to why he disagreed and criticized some aspects of Sufism. Relevant data to the study will be collected from print and internet sources. As a qualitative study, the content and textual-analysis methods will be used to analyze the pertinent data.